Avaliação do Risco de Quedas em Idosos na Perspectiva das Representações Sociais - Pinho, Tatyana Ataíde Melo de (2010)
Introduction: In the last decades it is been verified that the world population has been aging in an abrupt form, and the expectancy is that the longevity increase more and more and in a short period of time. This situation represents a great challenge for the competent organs and also for the society, highlighting the necessity of the creation of new public policies of health, aiming to offer a better quality of life to these elderly. One of the factors that can influence in the reduction of the quality of life of these people is the fall, which at the moment, due to high incidence, mortality, morbidity, and high social and economic costs, constitutes a serious problem of public health. Objectives: Knowing the social representations of the elderly attended in the health basic units about aging and risk of falls and evaluating the risk of falls in elderly. Methodology: It is an exploratory study in a quantitative-qualitative approach, done in the territory of the health family unit (HFU) Live Well , located in the neighborhood Treze de Maio, in the city of João Pessoa PB. The sample composed of one hundred and fifty elderly happened by convenience. As instruments an interview semi structured and the Fall Risk Score were used to evaluate the risk of falls. The period of data collection happened from January to April of 2009. The data collected of the interviews were analyzed from the Alceste 4.8 for the apprehension of the social representations about aging and risk of fall, afterwards interpreted according to the theoretical contribution of the social representations and for the analysis of the Fall Risk Score the SPSS 17.0. was used. Results:The analysis from the Alceste 4.8 retained 419 UCE S (64,4%), dividing the corpus in five classes. The representations of the elderly about the risk of falls and aging were permeated by dimensions much more negative that positive, like diseases, incapacities, dependence, loneliness, sadness, being represented as <<losses>> and <<incapacities>>, showing the difficulties lived by the elderly of the study facing this phase of the life. It was realized that most of the elderly (58,8%), of this study did not suffer falls, being, 63 of the elderly who fell, 71,4% said to have fallen once or twice, and the main intrinsic cause was dizziness/vertigo, while the extrinsic were sliding or wet floors. The data collected and analyzed were interpreted subsidized of the theoretical referential of the social representations. Final Considerations: The evaluation of risk of falls has a great importance in elderly in the perspective of the social representations, so that it serves of subsidies for the realization of preventive actions which aim the maximization of the quality of life of this population.